PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan Rias Pengantin Putri Ayu di Surakarta) - Lidia Sri Purwaningsih, Marjam Desma Rahadhini & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2018)
This research aims to analyze the significance of the influence of the quality of service to customer satisfaction on customer. To analyze the significance of the influence of the quality of service and customer satisfaction on customer loyalty. To analyze the significance of the influence of the quality of service of customer loyalty that is mediated by customer satisfaction. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research customers who use services in the Putri Ayu bridal makeup of Surakarta number no doubt is not known. The number of samples that are used i.e. 100 people, sampling techniques using a purposive sampling. Methods of data collection were used: questionnaire and documentation. Test instrument use test validity and reliability tests. Technique of data analysis using t-test analysis, F-test F, R² and path analysis. The research results obtained conclusions of influential service quality customer satisfaction significantly to bridal makeup Putri Ayu in Surakarta. Service quality and customer satisfaction significantly to influential customer loyalty bridal makeup Putri Ayu in Surakarta. Mediated influence customer satisfaction service quality against customer loyalty.Keywords: service quality, customer satisfaction, customer loyalty.